Equine dental and periodontal anatomy: A tutorial review. (13th February 2015) - Staszyk, C.; Suske, A.; Pöschke, A.
Summary A sound knowledge of dental and periodontal anatomy provides the basis for an accurate diagnosis of dental abnormalities. It must be remembered that dental and periodontal anatomy, especially in the horse, undergoes continuous morphological changes throughout life. From birth to age about 6 years the deciduous and later the permanent teeth emerge in turn through the oral mucosa. Even the permanent dentition is subjected to continuous, dynamic, morphological changes due to massive occlusal wear and the compensatory tooth eruption that is necessary in herbivores. Consequently, it is not surprising that the normal equine oral anatomy of structures shows a wide range of variations. The purpose of this tutorial article is to review and summarise the current knowledge of equine dental and periodontal anatomy, paying special attention to age related morphological changes.